Preparation and photoelectrochemical properties of nanostructuredmanganese-dopedcadmiumsulfide/ titania for solar cellapplication - Mohd Amin, Wardatun Nadrah (2018)
The outstanding properties of nanocryst alline semiconductor, titanium dioxide (TiO₂) such as low production cost, good chemical stability, non-toxicity and high photocurrent efficiency make it well accepted to mediate solar energy conversion. However, TiO₂ has limitation in absorbing sunlight’s visible spectrum due to its wide band gap. Moreover, there are issues such as high proportion of recombination of photogenerated electron-hole pairs which highly influence the photoelectrochemical performance. To overcome these problem inorganic sensitisation using metal chalcogenides were widely explored. CdS attracted so much interest in photoelectrochemical cell applications due to its high absorption coefficient, good direct band gap and excellent conversion efficiency. In this research, the effect of doping of manganese on the photoelectrochemical performance CdS sensitised TiO₂ was studied. The viscous paste of TiO₂ nanopowder was coated on the flourine-doped SnO₂ conductive glass via doctor-blade method, followed by calcination at 500 ᵒC. Polyester decomposition during calcination was found to be responsible for the formation of high quality crack free strongly adherent without delamination films. CdS was grown on TiO₂ by successive ionic layer adsorption (SILAR) technique by dipping the TiO₂ electrode alternately in two different solutions containing Cd²⁺and S²¯ precursors. SILAR technique has been carried out at varying SILAR cycles, dipping time, pH, concentrations of cationic precursor and annealing temperatures. CdS/TiO₂ prepared by depositing CdS using seven SILAR cycles with one min dipping time was found to show optimum optical absorption with the band gap of 2.238 eV. X-ray diffraction pattern showed that the deposited CdS on TiO₂ were polycrystalline with cubic structure. The CdS/TiO₂ was found to be n-type based on the photoelectrochemical (PEC) results. Mn-doped CdS was prepared using SILAR technique by introducing manganese salt into the cationic precursor solution in an effort to improve the photocurrent generation. The electrode fabrication was done at different SILAR cycles, manganese concentrations and annealing temperature. XRD patterns showed that the incorporation of manganese in CdS matrix of nanoporous TiO₂ structure shifted the diffraction peak of CdS to lower angle. The optical absorption results reveal that Mn-doping greatly enhanced the light absorption in the visible region. The band gap energy dropped from 2.238 eV to 1.680 eV. The photocurrent of the thin film increase by more than 30 % from 3.613 mA/cm² for CdS/TiO₂ to 5.477 mA/cm² for Mn-doped CdS/TiO₂. Mn-doped CdS/TiO₂ clearly showed tremendous increased in the photocurrent by more than 60 times compared to TiO₂ nanoparticles. Besides, other transition metals such as chromium, nickel and copper were doped with CdS on TiO₂ nanoparticles to compare the effect on the photoelectrochemical performance. It was found out that Mn doped CdS achieved the highest photoconversion efficiency with the value 4.025 % among the transition metals.